Treatment outcomes, quality of life, and impact of hemophilia on young adults (aged 18–30 years) with hemophilia. (December 2015) - Witkop, Michelle; Guelcher, Christine; Forsyth, Angela; Hawk, Sarah; Curtis, Randall; Kelley, Laureen; Frick, Neil; Rice, Michelle; Rosu, Gabriela; Cooper, David L.
Abstract : The Hemophilia Experiences, Results and Opportunities (HERO) initiative assessed psychosocial issues reported by people with moderate to severe hemophilia and was led by a multidisciplinary international advisory board. This analysis reports data from young adult respondents (aged 18–30 years), including both US and overall global (including US respondents) results, and investigates treatment outcomes, quality of life, and impacts of hemophilia on relationships. More young adults in HERO received prophylaxis than on‐demand treatment, although a majority reported not using factor products exactly as prescribed, and 50% of global respondents and 26% of US respondents reported issues with access to factor replacement therapy in the previous 5 years. Many young adults with hemophilia reported comorbidities, including bone/skeletal arthritis, chronic pain, and viral infections, and nearly half of young adults reported anxiety/depression. Most reported pain interference with daily activities in the past 4 weeks, although a majority reported participating in lower‐risk activities and approximately half in intermediate‐risk activities. Most young adults were very or quite satisfied with the support of partners/spouses, family, and friends, although roughly one‐third reported that hemophilia affected their ability to develop close relationships with a partner. A majority of young adults reported that hemophilia has had a negative impact on employment, and 62% of global respondents and 78% of US respondents were employed at least part‐time. Together these data highlight the psychosocial issues experienced by young adults with hemophilia and suggest that increased focus on these issues may improve comprehensive care during the transition to adulthood. Am. J. Hematol. 90:S3–S10, 2015. © 2015 Wiley Periodicals, Inc.